Unmasking microplastic pollution: a study on the distribution and impact of microplastics in Yuehai Lake, China - Ren, Jia; Li, YiChao; Wang, Yuwen; Yang, Huifang; Buyong, Faeiza (Faculty of Applied Sciences, 2025)
The increasing use of plastics has led to a significant environmental challenge: microplastic (MP) pollution, which poses threats to aquatic ecosystems and human well-being. Freshwater habitats, including lakes, are particularly vulnerable to such contamination. This study investigates the characteristics and distribution of microplastics (MPs) in Yuehai Lake, China. Water samples were collected from five locations and analyzed using laser direct infrared (LDIR) spectroscopy to assess MP presence and concentration. MPs were detected at all sampling sites. The highest concentration, exceeding 1400 particles/L, was recorded at S5 (Lijing Street), while S1 (Yuehai Fishing Base), a site primarily used for fishing activities, recorded a concentration of 1100 particles/L. MP fragments were the predominant form (63.36%), followed by fibers (33.22%) and films (3.42%). Seventeen polymer types were identified, with fluororubber (FKM) being the most common (22.80%), followed by fluorosilicone rubber (FVMQ, 16.90%), chlorinated polyethylene (CPE, 13.58%), and polyvinyl chloride (PVC, 10.10%). The composition and morphology of MPs suggest automobile tire contamination as a primary source. Over 90% of the MPs detected were small-sized particles (20–100 μm). The Pollution Load Index (PLI) confirmed MP contamination at all sites. These findings provide essential insights to support governmental initiatives in environmental protection, policy development, and public awareness, contributing to improved ecological health and sustainability.